(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the satisfaction of inpatients with medical meals at the National Hospital of Endocrinology in 2024. Subjects and research methods: A cross-sectional descriptive study was conducted on 196 inpatients using medical meals at the National Hospital of Endocrinology from July 2024 to December 2024. Patient satisfaction was assessed using a questionnaire with a 5-point Likert scale; patients were defined as satisfied if the total score was ≥ 70% of the maximum possible score. Results: The overall satisfaction rate of patients with medical meals was 67.3%. The highest satisfaction rates were observed for the eating environment and facilities (81.1%) and meal service operations (80.6%). Lower satisfaction rates were found for meal quality (66.3%) and cost (63.8%). Conclusion: The satisfaction rate of patients with medical meals is at a fair level; however, interventions are needed for further improvement, particularly regarding meal quality and cost.